DAMPAK PELATIHAN DAN PERGESERAN TUGAS PADA PERAWAT ICU DALAM MENGHADAPI TIGA GELOMBANG COVID-19 - Samantha; Fushen; Wani Devita Gunardi (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This case study research aims to determine the impact of training and task shifts on nurses serving in the ICU of Ukrida Hospital Jakarta in dealing with two waves of Covid-19. The approach used is a descriptive qualitative approach, with the type of research used is a case study. Sampling was purposive sampling and obtained through in-depth interviews with five nurse informants at UKRIDA Hospital. Data were analyzed by qualitative analysis method. The results of this study identified 3 major themes, namely nurse professionalism, dedication, and legality. In the discussion above, it can be concluded that the increasing need for personnel in the ICU during the COVID-19 pandemic can be overcome by training and shifting tasks on an ongoing basis.